Interventions among Pregnant Women in the Field of Music Therapy: A Systematic Review - Shimada, Bruna Mayumi Omori; Santos, Magda da Silva Oliveira Menezes dos; Cabral, Mayara Alvares; Silva, Vanessa Oliveira; Vagetti, Gislaine Cristina (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To investigate in the literature the studies on the benefits of music therapy interventions among pregnant women in the prenatal, delivery and postpartum periods.Data Sources The search for articles was carried out in the following electronic databases: VHL, LILACS, SciELO, Portal CAPES, PsycINFO, ERIC, PubMed/Medline, and journals specialized in this field: Revista Brasileira de Musicoterapia (“Brazilian Journal of Music Therapy”) and Voices.Study Selection Descriptors in Portuguese (musicoterapia, gravidez, gestantes, revisão), English (music therapy, pregnancy, pregnant women, review) and Spanish (musicoterapia, embarazo, mujeres embarazadas, revisión) were used. The search was delimited between January 2009 and June 2019. The process of selection and evaluation of the articles was performed through peer review.Data Collection The following data were extracted: article title, year of publication, journal, author(s), database, country and date of collection, purpose of the study, sample size, type of care, intervention, instruments used, results, and conclusion. The data were organized in chronological order based on the year of publication of the study.Summary of the Data In total, 146 articles were identified, and only 23 studies were included in this systematic review. The articles found indicate among their results relaxation, decreased levels of anxiety, psychosocial stress and depression, decreased pain, increase in the maternal bond, improvement in the quality of sleep, control of the fetal heart rate and maternal blood pressure, and decreased intake of drugs in the postoperative period.Conclusion Music therapy during the prenatal, delivery and postpartum periods can provide benefits to pregnant women and newborns, thus justifying its importance in this field.
Keywords: pregnancy; music therapy; music; women's health